Ketogenic Diet Administration Later in Life Improves Memory by Modifying the Synaptic Cortical Proteome Via the Pka Signaling Pathway in Aging Mice - Morales-Munoz, B; Contreras-Pacheco, D; Ampuero-Llanos, E (Cell Press, 2024)
Aging compromises brain function leading to cognitive decline. A cyclic ketogenic diet (KD) improves memory in aged mice after long-term administration; however, short-term effects later in life and the molecular mechanisms that govern such changes remain unclear. Here, we explore the impact of a short-term KD treatment starting at elderly stage on brain function of aged mice. Behavioral testing and long-term potentiation (LTP) recordings reveal that KD improves working memory and hippocampal LTP. Furthermore, the synaptosome proteome of aged mice fed a KD long-term evidence changes predominantly at the presynaptic compartment associated to the protein kinase A (PKA) signaling pathway. These findings were corroborated in vivo by western blot analysis, with high BDNF abundance and PKA substrate phosphorylation. Overall, we show that a KD modifies brain function even when it is administered later in life and recapitulates molecular features of long-term administration, including the PKA signaling pathway, thus promoting synaptic plasticity at advanced age. © 2024 The Author(s)